Quasi solid-state dye-sensitized solar cell with P(MMA-co-MAA)-based polymer electrolytes - Sundararajan, V.; Saidi, Norshahirah M.; Ramesh, Subramaniam; Ramesh, Kasi; Selvaraj, Gowri; Wilfred, Cecilia Devi (Springer Verlag (Germany), 2019)
A series of poly (methylacrylate-co-methylacrylic acid) (P(MMA-co-MAA)) gel polymer electrolytes containing iodide/triiodide (I − /I 3 − ) redox mediator from sodium iodide (NaI) dopant salt was synthesized and studied on their conductivity and power conversion efficiency as applied in dye-sensitized solar cells (DSSC). A relationship of complex permittivity with increasing frequency was established as well as dispersion relation with modulus studies. Temperature dependence study forms an Arrhenius plot and the highest ionic conductivity achieved was 1.07 mS cm −1 at room temperature with activation energy of 0.224 eV for the gel polymer electrolytes (GPE) with 40 wt% NaI. Fourier transform infrared (FTIR) and X-ray diffraction (XRD) spectroscopy was utilized to evaluate the formation of complexes between the copolymer and salt. Again at 40 wt% NaI, the best performance was observed under photovoltaic investigation using DSSC with energy conversion efficiency of 2.34%. To further understand the electrochemical properties of the GPE, steady-state measurement of triiodide diffusion coefficient was done. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.